Ten years of biosimilar recombinant human growth hormone in Europe - Saenger P (Dove Medical Press, 2017)
Paul Saenger Division of Pediatric Endocrinology, Department of Pediatrics, Winthrop University Hospital, Mineola, NY, USA Abstract: Recombinant human growth hormone (rhGH) has been in clinical use for more than 30 years. With the expiration of patent exclusivity for the first wave of rhGH products and other biopharmaceuticals, the opportunity emerged for the development of biosimilar medicines. A biosimilar is defined by the European Medicines Agency (EMA) as a biological medicine that is similar to another biological medicine that has already been authorized for use. The EMA led the way (well ahead of the Food and Drug Administration in the US) in developing the biosimilar concept, and the type of science-based regulatory framework required to ensure high-quality, safe, and effective biosimilar medicines; the provisions for approval of biosimilars have been in place in Europe since 2005. Under these provisions, Omnitrope® was approved by the EMA in 2006 as the world’s first biosimilar medicine; 2016 therefore marks the 10th anniversary of its approval in Europe. A substantial data set, based on clinical development studies and 10 years of postapproval use, has now accumulated for biosimilar rhGH; this data set shows that the product is an effective treatment option for children who require rhGH treatment, and has a safety profile that is consistent with the rhGH class. The decade since the EMA approved biosimilar rhGH has seen the successful approval and clinical use of 20 biosimilar medicines, confirming the integrity of the scientific basis for the biosimilar concept, as well as the quality of regulatory decision-making. Keywords: recombinant human growth hormone, Omnitrope®, biosimilar